(untitled) (World Bulletin of Social Sciences, 2025)
In the digital age, the abundance of information sources necessitates effective critical evaluation skills to discern credible from unreliable content. The CRAAP model—focusing on Currency, Relevance, Authority, Accuracy, and Purpose— has emerged as a widely used framework to guide information literacy. This article examines the theoretical foundations, practical application, and contemporary relevance of the CRAAP model. Using qualitative analysis of academic literature and educational practices, the study explores how the model facilitates critical thinking and promotes information competence among learners. Results highlight the model’s adaptability across disciplines and media types, while also discussing its limitations in addressing emerging challenges such as misinformation and bias in digital contexts. The article concludes with recommendations to enhance the CRAAP model’s efficacy in developing critical information evaluation skills in an evolving information landscape.